Swot analysis : Reference department / Abdul Azim Ab. Ghani - Ab. Ghani, Abdul Azim (Faculty of Information Management, 2014)
Library is a place where users can find current, accurate and valuable information and knowledge. Usually, the information in the library is provided by the professional in a certain fields. Their information can be used for the research paper. Academic libraries have been comfortably serving their clientele by providing information resources and services to fulfill the needs of students and researchers, Kiran (2009). Each of institutions should have their own library to fulfill their students need in information and for their studies. Reference Department is one of the units in the library that is very important to support the library mission. Reference and Resource Coordination Department is to support the library's mission by developing the library's collections; providing liaison services to the faculty; and instructing and assisting patrons in the location, use, and evaluation of information sources, Sarah and Gary (2009). Glaister and Falshaw (2009) on Marilyn, Martin, Lisandro and William (2011) article say, SWOT analysis is categorizing strengths, weaknesses, opportunities and threats into most respected and prevalent tools of strategic planning. With SWOT analysis, an organization can identify what is their strength, weakness, opportunity and threat of their organization. This SWOT Analysis is done by me, through the interview from the staff in the Reference Department. I have gather all the information from the staff which is En Ali Anuar B Yaakob , the Assistant Librarian, Nurul Zalila Binti Ismail, Library Assistant and En Ahmad Syarifuddin Bin Ruspin.